1999
DOI: 10.1136/sti.75.6.431
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the prevalence of Trichomonas vaginalis, Chlamydia trachomatis, Neisseria gonorrhoeae, and human papillomavirus infection in indigenous women in northern Australia

Abstract: Objective: To estimate more accurately the age specific prevalence of Trichomonas vaginalis, Chlamydia trachomatis, Neisseria gonorrhoeae, and human papillomavirus infection (HPV) in indigenous women living in urban, rural, and remote areas of the "Top End" of the Northern Territory (NT). Design: Analysis of data obtained from two community based studies using self administered tampon specimens tested by polymerase chain reaction for sexually transmitted disease (STD). Data pertaining to the notifiable STDs (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 18 publications
4
55
1
Order By: Relevance
“…Our methods will have under-represented Indigenous Australians in remote communities, among whom high STI prevalence has been found. [44][45][46][47][48] Methods other than telephone surveys may be better suited to collecting information from remote Indigenous populations. A strength of the random digit dialling method over selecting from directories was that households with silent or unlisted numbers were within the scope of the survey.…”
Section: The Computer-assisted Telephone Interview (Cati) Used In Thementioning
confidence: 99%
“…Our methods will have under-represented Indigenous Australians in remote communities, among whom high STI prevalence has been found. [44][45][46][47][48] Methods other than telephone surveys may be better suited to collecting information from remote Indigenous populations. A strength of the random digit dialling method over selecting from directories was that households with silent or unlisted numbers were within the scope of the survey.…”
Section: The Computer-assisted Telephone Interview (Cati) Used In Thementioning
confidence: 99%
“…Chronic infections have been associated with pre-term birth and low birth-weight neonates, cervical cancer and increased HIV transmission amongst the most alarming [16][17][18]. Infection rates have been reported as high as 67% in Mongolia in 1998 [19], 40-60 % in Africa, 40% in Indigenous Australians over 40 years of age [20], and 46% in highland women of Papua New Guinea [21,22]. Trichomoniasis has the highest prevalence and incidence of any STI, and its eradication may well be the single most cost-effective step in HIV incidence reduction [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In the north of Australia, the authors have found that a study carried out on aboriginal women has found an increase in the prevalence of the infection in T. vaginalis with age. 12,13 According to other authors, unlike Chlamydia trachomatis and N. gonorrhoeae, the young age is not a risk factor of trichomoniasis. The prevalence of T. vaginalis appears to increase with age for both sexes, perhaps due to the nature frequent asymptomatic infection and consequently the persistence of untreated infections.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of T. vaginalis appears to increase with age for both sexes, perhaps due to the nature frequent asymptomatic infection and consequently the persistence of untreated infections. 12 The unprotected sex with multiple partners increases the chances of an infection by T. vaginalis, as other STI. There is no doubt that the protection of sex with a condom helps to prevent the vaginal infection of T. vaginalis as well as other STI.…”
Section: Discussionmentioning
confidence: 99%